Risk and protective factors for obstetric anal sphincter injuries: A retrospective nationwide study. Issue 4 (14th March 2018) - Marschalek, Marie‐Louise; Worda, Christof; Kuessel, Lorenz; Koelbl, Heinz; Oberaigner, Willi; Leitner, Hermann; Marschalek, Julian; Husslein, Heinrich
Abstract: Background: In view of the reported increase in obstetric anal sphincter injuries, the objective of this study was to evaluate the incidence of such injuries over time and the associated risk and protective factors. Methods: This was a retrospective cohort study from a national database of 168 137 primiparous women with term, singleton, cephalic, vaginal delivery between 2008 and 2014. The main outcome measure was obstetric anal sphincter injury. A multivariate regression model was used to identify risk and protective factors. Results: Age >19 years, birthweight >4000 g, and operative vaginal delivery were independent risk factors for obstetric anal sphincter injuries. Mediolateral episiotomy increased the risk for obstetric anal sphincter injuries in spontaneous vaginal birth (number needed to harm 333), whereas it was protective in vacuum delivery (number needed to treat 50). From 2008 to 2014, there was an increase in the rate of obstetric anal sphincter injuries (2.1% vs 3.1%, P < .01), vacuum deliveries (12.1% vs 12.8%, P < .01), and cesarean delivery after labor (17.1% vs 19.4%, P < .01), while forceps deliveries (0.4% vs 0.1%, P < .01) and episiotomy rate decreased (35.9% vs 26.4%, P < .01). Conclusions: Episiotomy may be a risk or protective factor depending on the type of episiotomy and the clinical setting in which it is used. Our study supports a restrictive use of mediolateral episiotomy in spontaneous vaginal deliveries. In vacuum deliveries mediolateral episiotomy may help prevent obstetric anal sphincter injuries.